PENGARUH PENERAPAN FILM ANIMASI RIKO THE SERIES TERHADAP KEMAMPUAN MENGHAFAL DOA-DOA HARIAN ANAK USIA DINI(Penelitian Pre-Experimental di Kelompok B RA Baitur Rahim Kecamatan Andir KotaBandung) - Yulia Yasmin; Heri Hidayat (CV. ADIBA ASIHA AMIRA, 2025)
This study is motivated by the problems that occur, namely children's difficulty in remembering and memorizing daily prayers. Therefore, researchers chose to use the animated film Riko The Series to determine its effect on the ability to memorize daily prayers of early childhood. This research is based on a thought in developing memorization skills using animated media. Riko The Series animated film contains educational entertainment related to the Qur'an and daily prayers, so it can be used for children to memorize daily prayers in a fun way in terms of the benefits provided by the animated film. The results showed that the ability to memorize daily prayers of early childhood using the animated film Riko The Series in group B on prayer when it rains obtained an average pretest score of 50 which was interpreted in the poor category and obtained an average posttest score of 78 which was interpreted in the good category. The t test results obtained tcount> ttable with a value of 11.337> 2.055 at a significance level of 5% then the hypothesis H0 is rejected and Ha is accepted. That is, there is an effect of the application of the animated film Riko The Series on the ability to memorize daily prayers of early childhood in group B RA Baitur Rahim Andir District, Bandung City. While the results of research on the ability to memorize daily prayers of early childhood using animated films Riko The Series in group B on prayers to both parents obtained an average pretest score of 52 which was interpreted in the poor category and obtained an average posttest score of 70 which was interpreted in the good category. The t test results obtained tcount> ttable with a value of 10.015> 2.055 at a significance level of 5% then the hypothesis H0 is rejected and Ha is accepted. That is, there is an effect of the application of the animated film Riko The Series on the ability to memorize daily prayers of early childhood in group B RA Baitur Rahim, Andir District, Bandung City.